Evaluation of the Performance of BAPPEDA Gayo Lues Regency in the Process of Preparing the Regional Development Work Plan - Adam, Saleh; Kelana, Edy Putra; Akadira, Tora (Riwayat: Educational Journal of History and Humanities, 2024)
The Gayo Lues Regency Government Work Plan (RKPK) is a planning document prepared as a guide for the implementation of the Gayo Lues Regency Budget and Revenue and Expenditure. BAPPEDA as an agency that has the duties, principals and functions of planning regional development in the focus of RKPD planning includes situation analysis, formulation of vision, mission and objectives, identification of programs and activities, budgeting, public consultation and approval. This research aims to analyze the performance of BAPPEDA in the process of preparing the RKPK and the factors that influence the process of preparing it. The theory used is the Organizational Performance theory according to Agus Dwiyanto with indicators of productivity, responsiveness and accountability. The research method uses a qualitative approach. The research results show that the performance of BAPPEDA Gayo Lues in the RKPK preparation process is still not optimal, this is due to the implementation of the RKPK preparation from preparation to completion not being on time, as well as inconsistencies between the RKPK and the KUA/PPAS and the RAPBD. In the productivity aspect, it is known that BAPPEDA's performance greatly determines the success in preparing the District Development Work Plan. The problem that occurs is the RKPK not being completed on time according to the specified targets. Factors that influence BAPPEDA's responsiveness include human resources, sufficient budget and collaboration with stakeholders. by external factors such as political intervention which results in a lack of transparency and affects public accountability. The internal factor that influences the performance of BAPPEDA Gayo Lues Regency is that the number of human resources who are expert planners is still very minimal and the workload is not balanced with the number of human resources, while the external factor that influences the performance of BAPPEDA Gayo Lues Regency is the influence of political bureaucracy in preparing the RKPK which also influences the inconsistency of the RKPK